Customers’ attitude toward message effectiveness on newspaper advertising of Naza Kia Malaysia Sdn. Bhd / Muhammad Hanif Hasan - Hasan, Muhammad Hanif (2012)
Traditional advertising media such as TV, Radio, Press, and Outdoor advertisements are losing their ability to transfer information and persuade people to buy products but interactive advertising media such as Website, Social Media, interactive TV and mobile devices are getting more powerful. So, the main problem for this study is to study and examine what are the determinants that will increase the level of message effectiveness on newspaper advertising for Naza Kia Malaysia Sdn. Bhd. This research is applying a descriptive research where the researcher investigate whether the independent variable have a relationship with the dependent variable. The independent variable studied are entertainment, informative, irritation, credibility and economic and method use is distributing questionnaire to 235 respondents. The analysis shows that all the independent variable (IV) is significant with dependent variable (DV). From R2 it show that 51.4 % explained all the independent variable (IV) which is entertainment, informative, irritation, credibility, economic are highly influence the dependent variable (DV), customers’ attitude toward message effectiveness on newspaper advertising of Naza Kia Malaysia Sdn. Bhd. Meanwhile only 48.6 % are been explain by other factors. All the null hypotheses have been rejected. Based on the result obtain, it can be conclude that newspaper advertising is still relevant to be expand in the industry especially in marketing activity and campaign